Old Proverbs in New Skins – An fMRI Study on Defamiliarization - Bohrn, Isabel C.; Altmann, Ulrike; Lubrich, Oliver; Menninghaus, Winfried; Jacobs, Arthur M. (Frontiers in Psychology, 2012)
We investigated how processing fluency and defamiliarization contribute to the affective and aesthetic processing of reading in an event-related fMRI experiment with 26 participants. We compared the neural correlates of processing (a) familiar German proverbs, (b) unfamiliar proverbs, (c) twisted variations which altered the concept of the original proverb (anti-proverbs), (d) variations with incorrect wording but the same concept as the original proverb (violated proverbs), and (e) non-rhetorical sentences. We report processing differences between anti-proverbs and violated proverbs. Anti-proverbs triggered a process of affective evaluation relying on self-referential thinking and semantic memory in contrast to violated proverbs, which recruited the frontotemporal attention and error detection network. In consistence with the coarse semantic coding theory, proverb familiarity affected lateralization: relative to non-rhetorical sentences highly familiar proverbs activated the left parahippocampal gyrus, whereas unfamiliar proverbs activated an extensive network, covering bilateral frontotemporal cortex. Despite affective processing being enhanced for anti-proverbs, familiar proverbs received the highest beauty ratings. Effects of familiarity and defamiliarization on the aesthetic perception of literature will be discussed.